De musica libellus/Tractatus de discantu/Compendium discantus/Traitié de deschant - Reaney, Gilbert (American Institute of Musicology, 1996)
a) ANONYMOUS, De musica libellus.b) ANONYMOUS, Tractatus de discantu.c) PSEUDO-FRANCO DE COLONIA, Compendium discantus.d) ANONYMOUS, Traitié de deschant.e) ANONYMOUS, Traitié de deschant.
Keywords: Music theory